2009
DOI: 10.1073/pnas.0912966107
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased probing of the entire hepatitis C virus life cycle identifies clinical compounds that target multiple aspects of the infection

Abstract: Over 170 million people are chronically infected by the hepatitis C virus (HCV) and at risk for dying from liver cirrhosis and hepatocellular carcinoma. Current therapy is expensive, associated with significant side effects, and often ineffective. Discovery of antiviral compounds against HCV traditionally involves a priori target identification followed by biochemical screening and confirmation in cell-based replicon assays. Typically, this results in the discovery of compounds that address a few predetermined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 49 publications
5
135
0
Order By: Relevance
“…17 Pharmacological in vitro research suggests the distal sterol pathway is important for the HCV lifecycle and raises the potential for more selective inhibition of HCV replication by targeting this with small molecules and sterol antagonists. 36,37 Our data would support this. Further targeted, in vitro studies are indicated to better identify the specific point(s) and nature of HCV interference in late cholesterol biosynthesis.…”
Section: Discussionsupporting
confidence: 73%
“…17 Pharmacological in vitro research suggests the distal sterol pathway is important for the HCV lifecycle and raises the potential for more selective inhibition of HCV replication by targeting this with small molecules and sterol antagonists. 36,37 Our data would support this. Further targeted, in vitro studies are indicated to better identify the specific point(s) and nature of HCV interference in late cholesterol biosynthesis.…”
Section: Discussionsupporting
confidence: 73%
“…Reporter viruses make such assays adaptable to high-throughput screening, with obvious advantages for antiviral research [76,126,[129][130][131]. Figure 4 illustrates a possible assay setup based on a dual reporter system, typically the Gaussia/Renilla and firefly luciferases.…”
Section: The Cell-cultured Hcv (Hcvcc) System and Derivativesmentioning
confidence: 99%
“…Moreover, chlorcyclizine inhibits HCVcc but not HCVpp (6). In contrast, some phenothiazines, like fluphenazine, trifluoperazine, and prochlorperazine, inhibit both particle types (4,5,21). These observations show that there may be subtle differences in the ways that these structurally related drugs inhibit HCV.…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 68%
“…Since HCV infects cells by using the endocytic pathway (10), it is reasonable to assume that chlorpromazine and possibly also related compounds inhibit HCV and other viruses by disrupting this process (4,10). While this may be the case for chlorpromazine and its antiviral activity toward HCV and other viruses, this is, however, unlikely to be the primary antiviral mechanism for related phenothiazines, like fluphenazine and trifluoperazine, and for flunarizine, a structurally similar diphenylpiperazine (7).…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
See 1 more Smart Citation